Synthesis of New Azole Phosphonate Precursors for Fuel Cells Proton Exchange Membranes - Teixeira, António P. S. (2016)
Herein we present the synthesis and characterization of new phosphonate-, bisphosphonate- and hydroxybisphosphonatebenzimidazole derivatives substituted at the N-1 position and new regioisomers phosphonate-, bisphosphonate-, and hydroxybisphosphonatebenzotriazole derivatives substituted at N-1 or N-2 positions. The compounds were characterized by NMR and IR spectroscopies, and mass spectrometry (low and high resolution) allowing the assignment of their structure, including the identification of regioisomers. These new azole monomers will be precursors for a mesoporous silica host to produce novel membrane materials with high proton conductivity for intermediate temperature proton exchange membrane fuel cells.